Space-Focused Stereotypes and Their Potential Role in Group-Based Disparities in Social Work Services - Iniobong Essien; Birte Siem (Social Work and Society, 2025)
Despite social work's unique commitment to diversity, several findings suggest group-based disparities in social work services. To explain such disparities, theories in social psychology emphasize the role of stereotypes. The present article focuses on how stereotypes among social work professionals might affect the client-provider dyad, paying particular attention to the diversity dimensions of"race" and ethnicity. We first introduce a traditional conceptualization of group-based stereotypes and then derive how stereotypes may also be applied to physical spaces. We next elaborate on how social work professionals' mental images of racialized spaces might contribute to disparities, using the example of child welfare decision-making. We argue that space-focused stereotypes might contribute to disparities by affecting social work professionals' perceptions, judgement, and treatment of (1) space itself and (2) clients. Finally, we discuss how a space-focused perspective on stereotypes may inform prevention and intervention approaches that might go unnoticed in a traditional conceptualization of stereotypes as solely group-based phenomena.